STUDI PENERAPAN SEMA NO. 1 TAHUN 2017 DI PENGADILAN AGAMA TALU - Elimartati; Firdaus; Ahmad Julio Saputra (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2021)
The Supreme Court Circular No. 1 of 2017 aims to provide legal protection for women's rights after divorce. But in its implementation women's rights are neglected. Wives are often in an attenuated position. The problem in this paper is between the expectations and challenges of the execution of the living in the pronunciation of the divorce pledge no. 121/Pdt.G/2018/PA TALU which is not carried out by the husband. The research method uses a gender analysis approach. Data is collected based on observations, interviews and documents. The findings in this study are three conditions in which all three cannot provide justice to women's rights. First; the husband does not execute the judge's decision on the obligation of living set by the judge of the Talu Religious Court, the pledge of divorce cannot be carried out, the marriage remains valid but the husband and wife are not home anymore and the wife never again earns a living. Second; If the sincere wife does not get her rights after the divorce, then the judge can witness the divorce pledge of the husband finally occurs divorce. Third; when the research was done the husband had done siri marriage. Women become psychologically and materially victimized in the absence of efforts to seek justice (dead ends). The best solution is to expect the husband's awareness of his responsibility to provide a living which is his obligation, will be accounted for before Allah SWT. In certain circumstances divorce is the best solution so that both regardless of the burden of birth and mental suffering, do not cause greater mafsadah. SEMA's goal of protecting the rights of wives is not in fact also achieved.